Irreversible electroporation for tissue ablation: A 3D computational platform - Sudip Kumar Das; Srinivasan Jayaraman (Computer Methods and Programs in Biomedicine Update)
Background and objective:: Globally, irreversible electroporation (IRE) emerges as a promising technique for tissue ablation as it overcomes the limitations of the benchmark techniques. However, achieving the desired and safe ablation volume of tissue pivots on multiple factors, such as pulse profile, shape, and number of electrodes, besides the IRE treatment parameters, like pulse type, field strength, number of pulses, pulse length, and frequency. This work aims to develop a 3D computation platform that predicts the ablation volume using the IRE procedure and provides insights such as electric field, temperature and its corresponding cell survival regions. Thereby, such a platform aids in selecting optimized treatment parameters to avoid thermal damage. In addition, the developed IRE model estimates the relationship between the pulse protocol and different electrode geometries, number of electrodes, and electrode configurations. Methods:: The computational model for IRE is developed with Laplace’s equation and Penn’s bio-heat equation for the electric potential and temperature profiles, respectively, and the Finite Difference method is considered for the numerical solution. The statistical Fermi equation-based Peleg model has been adapted to estimate the ablation volume as a function of the magnitude of the electric field and other electric field parameters. Results:: The tissue ablation platform allows computation and visualization of ablation volume estimation using the IRE technique with a pair of plate-type and multiple pairs of needle-type electrodes. IRE treatment with different combinations of electric pulse parameters, i.e., pulse length, voltage, and number of pulses, causes different levels of temperature rise. By adapting our platform, one can avoid thermal damage in the IRE treatment with the right combination of pulse parameters. For instance, one can apply a maximum of 10 pulses restricting temperature within 50°C in the IRE treatment of cervical tissue with a couple of pairs of needle-type electrodes and 100μs electric pulses of 3000V. Conclusion:: The proposed IRE model aids in treatment planning for tissue ablation with 3D visual outputs through the platform’s user interface for better clinical insights, including interpretability, data resolution, and computational cost.